Molecular Identification and Drug Susceptibility of Leishmania spp. Clinical Isolates Collected from Two Regions of Oaxaca, Mexico - Adriana Moreno-Rodríguez; Ada Sarai Martin del Campo-Colín; Luis Roberto Domínguez-Díaz; Ana Livia Posadas-Jiménez; Félix Matadamas-Martínez; Lilián Yépez-Mulia (Microorganisms)
Pentavalent antimonials are the first line for leishmaniasis treatment, although they induce many adverse side effects and treatment failure and parasite resistance have been detected. Cutaneous leishmaniasis is the main clinical manifestation of the disease in Oaxaca State, Mexico; however, its presence is under-registered, and information about the Leishmania species that circulate and cause the disease in the region is limited. In this study, the presence of Leishmania was analyzed in 24 skin smears and 2 biopsies from lesions suspicious for leishmaniasis in inhabitants of the Tehuantepec Isthmus and Papaloapan Basin regions, Oaxaca State. By ITS1-PCR, the species of clinical isolates were identified. Moreover, the susceptibility of clinical isolates to leishmanicidal drugs was assessed. Skin smears were negative for the presence of Leishmania spp.; meanwhile, parasite amastigotes were observed in tissue biopsies; however, by ITS1-PCR, 46% of the samples were determined to be positive for the parasite. Six clinical isolates were identified as L. mexicana and had lower susceptibility to Miltefosine and Amphotericin B than the L. mexicana reference strain. No leishmanicidal activity of Glucantime was detected. Further studies with increased patient sample sizes and genotypic studies will describe in detail parasite susceptibility to reference drugs in the region.